Metal-Free Synthesis of 1-(α-Hydroxyindole)-o-carboranes in Neat - Zhang, Lin-Gen; Yuan, Wen; Yan, Shunsheng; Cao, Ke (Synthesis, 2025)
An efficient and environmentally friendly protocol for the synthesis of 1-(α-hydroxyindole)-o-carboranes has been developed via Friedel–Crafts reaction of C3-H of indoles with 1-formyl-o-carborane in the absence of Lewis acid and solvent. The intermolecular σ-π interaction between indole and B–H bonds of o-carborane was proposed for promoting the Friedel–Crafts reaction of the C3-H of indole.
Keywords: carborane; indole; Friedel–Crafts reaction; metal-free reaction; 1-(α-hydroxyindole)-o-carborane